The spruce budworm, Choristoneura fumiferana (Lepidoptera: Tortricidae), in British Columbia - Shore, T. L.; Alfaro, R. I. (The Entomological Society of British Columbia, 2019)
The spruce budworm, Choristoneura fumiferana (Clements), causes severe defoliation, primarily of white spruce, Picea glauca (Moench) Voss, eastern larch, Larix laricina (Du roi), K. Koch, and alpine fir, Abies lasiocarpa (Hook.) Nutt, in the Liard River area of northern British Columbia. Less preferred hosts are black spruce, Picea mariana (Mill.) B.S.P., and lodgepole pine, Pinus contorta Doug]. Infestations last for many years with variable defoliation intensity. Defoliation causes extensive top-killing of trees but little mortality. In addition, mature spruce trees (104 to 144 years old) defoliated from 1959 to 1976 lost an estimated 3 to 4.4% of diameter growth. Tree ring analysis suggested that C. fumiferana defoliated trees in the Liard River area at least five times since 1869. Infestations recurred every 14 to 28 years.